Bone remodeling at implants with different configurations and placed immediately at different depth into extraction sockets. Experimental study in dogs. Issue 5 (2nd June 2014) - Calvo‐Guirado, José Luis; Gomez Moreno, Gerardo; Aguilar‐Salvatierra, Antonio; Mate Sanchez de Val, Jose Eduardo; Abboud, Marcus; Nemcovsky, Carlos E.
Abstract Objectives This study evaluated the effect of implant macrodesign and position, related to the bone crest, on bone‐to‐implant contact (BIC) and crestal bone (CB) in immediate implants. Material and methods The study comprised of six foxhound dogs in which 48 immediate implants were placed. Three types of implants from the same manufacturer with similar surface characteristics but different macrodesigns were randomly placed: Group A (external hex with no collar microthreads), Group B (internal hex and collar microrings), and Group C (internal conical connection and collar microrings). Half of the implants were placed leveled with the bone crest (control) and the remaining, 2 mm subcrestally (test). Block sections were obtained after 12 weeks and processed for mineralized ground sectioning. Statistical analysis consisted of nonparametric Friedman and Wilcoxon test. Results All implants were clinically stable and histologically osseointegrated. Mean BIC percentage within the control group was as follows: A: 42.52 ± 8.67, B: 35.19 ± 18.12, and C: 47.46 ± 11.50. Within the test group: A: 47.33 ± 5.23, B: 48.38 ± 11.63, and C: 54.88 ± 11.73. Differences between each subgroup in the test and the control groups were statistically significant. BIC was statistically significantly higher in the test (50.588 ± 8.663) than in the control (43.317 ± 9.851) group. Within both groups, differences between group C and the other 2 were statistically significant. Distance from the implant shoulder to the buccal CB was statistically significantly larger in the control than in the test group and between subgroups B and C in the control and test groups. Within the test groups, relative bone gain was noticed. Conclusions Subcrestal immediate implant positioning may lead to a relatively reduced CB resorption and increased BIC. Implants macrodesign with crestal microrings may enhance BIC in post‐extraction implants.